2022
DOI: 10.1038/s41419-022-04855-0
|View full text |Cite|
|
Sign up to set email alerts
|

Halting ErbB-2 isoforms retrograde transport to the nucleus as a new theragnostic approach for triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is clinically defined by the absence of estrogen and progesterone receptors and the lack of membrane overexpression or gene amplification of receptor tyrosine kinase ErbB-2/HER2. Due to TNBC heterogeneity, clinical biomarkers and targeted therapies for this disease remain elusive. We demonstrated that ErbB-2 is localized in the nucleus (NErbB-2) of TNBC cells and primary tumors, from where it drives growth. We also discovered that TNBC expresses both wild-type ErbB-2 (WTErb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Additionally, the eviction from the nucleus or the silencing of isoform c blocked tumor growth, highlighting the dominant oncogenic potential of isoform c and suggesting both canonical and alternative isoforms of ErbB-2 as therapeutic targets in TNBC [ 25 ]. Another study showed that the use of inhibitors of the retrograde transport Retro-2 and its cyclic derivative Retro-2.1 not only blocked NErbB-2 retrograde transport but also suppressed TNBC growth in vitro, ex vivo, and in vivo, suggesting R2 as a potential novel therapeutic agent for TNBC [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the eviction from the nucleus or the silencing of isoform c blocked tumor growth, highlighting the dominant oncogenic potential of isoform c and suggesting both canonical and alternative isoforms of ErbB-2 as therapeutic targets in TNBC [ 25 ]. Another study showed that the use of inhibitors of the retrograde transport Retro-2 and its cyclic derivative Retro-2.1 not only blocked NErbB-2 retrograde transport but also suppressed TNBC growth in vitro, ex vivo, and in vivo, suggesting R2 as a potential novel therapeutic agent for TNBC [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the B2B1 model, NES-harboring cargoes were distinguished only when RanBP3 abundances were very high (Fig. 6a), allowing us to ignore consideration of ErbB–CRM1 interactions 77, 78 in this setting. Further simplifying the analysis, we found that the sensitivities of monopartite (NLS SV40Tag ) and bipartite (2xNLS Cbp80 ) NLS cargoes were identical except for an offset in N/C ratios from differences in affinity for Imp-α:Imp-β (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has recently been elucidated that in some instances of TNBC, HER2 is localised to the nucleus, where it can drive cancer growth due to its role as a transcription factor [185]. However, Madera et al show that the RT inhibitor, Retro-2, induces an accumulation of HER2 at the plasma membrane or Golgi, depending on the HER2 isoform, resulting in a significant reduction in cell growth [186].…”
Section: Her2mentioning
confidence: 99%
“…Retro-2 has emerged as a compound for therapeutically targeting a broad spectrum of RT cargo including bacterial toxins, viruses and RTKs [83,170,186,197,198]. Furthermore, the Retro-2 derivative, Retro-2.1, which is more potent than the parent form, is also being investigated for treatment against herpes simplex virus and polyomavirus in vitro, and more recently in vivo [197][198][199].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation